The micronutrient content of the diet is correlated with serum glucose biomarkers and lipid profile and is associated with the odds of being overweight/obese—a case-control study - Vahid, Farhad; Rahmani, Wena; Davoodi, Sayed Hossein; Bohn, Torsten (Frontiers in Nutrition, 2023)
A low micronutrient intake has been reported to contribute to the double-burden of obesity, increasing the risk for chronic diseases such as cardiovascular disease, diabetes, cancer, and mental disorders. This case-control study compared micronutrient intake-profiles in overweight/obese versus normal-weight individuals. We hypothesized that a low intake of certain micronutrients would increase the odds of being overweight/obese. Methods: The case group (n=812 adults) consisted of individuals with a BMI of 25 kg/m2, and the control group (n=793) had BMIs of 17.9-24.9 kg/m2. A validated 124-item food frequency questionnaire was used to determine micronutrient-related dietary-quality, using the index of nutritional quality (INQ), calculated as the fraction of a micronutrient consumed vs. its dietary requirement. In addition, body surface area (BSA) was calculated according to the Mosteller formula. Results: The control group had significantly higher INQ-scores of vitamin A, vitamin C, calcium, magnesium, and selenium compared to the case group. Furthermore, individuals with normal BSA (≤1.91m2 for men; ≤1.71 m2 for women) had significantly higher INQ scores of vitamin C, calcium, magnesium, and zinc compared to participants with high BSA. In multivariable adjustment regression models, INQs of vitamin C (ORBMI=0.79, 95%CI: 0.64-0.97; ORBSA=0.81, 95%CI, 0.68-0.97) and magnesium (ORBMI=0.69, 95%CI: 0.47-0.99; ORBSA=0.71, 95%CI: 0.52-0.97) were significantly associated with the odds of obesity/overweight (in both BMI and BSA categories). Conclusion: The significant association between micronutrient levels of the diet, especially of vitamin C and magnesium with both obesity criteria emphasized the importance of certain micronutrients in the obesity/overweight causal network.